A success in Toxinology translational research in Brazil: Bridging the gap - Ferreira, Ana Silvia Sartori Barraviera Seabra [UNESP]; Barraviera, Benedito [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP]; Caramori, Carlos Antonio [UNESP]; Ferreira, Rui Seabra [UNESP] (Elsevier, 2013)
Basic research is fundamental for discovering potential diagnostic and therapeutic tools, including drugs, vaccines and new diagnostic techniques. On this basis, diagnosis and treatment methods for many diseases have been developed. Presently, discovering new candidate molecules and testing them in animals are relatively easy tasks that require modest resources and responsibility. However, crossing the animal-to-human barrier is still a great challenge that most researchers tend to avoid. Thus, bridging this current gap between clinical and basic research must be encouraged and elucidated in training programmes for health professionals. This project clearly shows the challenges faced by a group of Brazilian researchers who, after discovering a new fibrin sealant through 20 years of painstaking basic work, insisted on having the product applied clinically. The Brazilian government has recently become aware of this challenge and has accordingly defined the product as strategic to the public health of the country. Thus, in addition to financing research and development laboratories, resources were invested in clinical trials and in the development of a virtual platform termed the Virtual System to Support Clinical Research (SAVPC); this platform imparts speed, reliability and visibility to advances in product development, fostering interactions among sponsors, physicians, students and, ultimately, the research subjects themselves. This pioneering project may become a future model for other public institutions in Brazil, principally in overcoming neglected diseases, which unfortunately continue to afflict this tropical country. © 2013 Elsevier Ltd.
Keywords: Fibrin sealant; GAP; Translational potential; Translational research; fibrin glue; vaccine; basic research; biomedicine; Brazil; clinical research; diagnostic procedure; drug design; drug development; education program; funding; health practitioner; human; information processing; neglected disease; nonhuman; priority journal; toxinology; translational research; tropics; Animalia